A large factory-scale application of selected autochthonous lactic acid bacteria for PDO Pecorino Siciliano cheese production. (October 2016) - Guarcello, Rosa; Carpino, Stefania; Gaglio, Raimondo; Pino, Alessandra; Rapisarda, Teresa; Caggia, Cinzia; Marino, Giovanni; Randazzo, Cinzia L.; Settanni, Luca; Todaro, Massimo
Abstract: The main hypothesis of this study was that the autochthonous lactic acid bacteria (LAB) selected for their dairy traits are able to stabilize the production of PDO (Protected Denomination of Origin) Pecorino Siciliano cheese, preserving its typicality. The experimental plan included the application of a multi-strain lactic acid bacteria (LAB) culture, composed of starter ( Lactococcus lactis subsp. lactis CAG4 and CAG37) and non starter ( Enterococcus faecalis PSL71, Lactococcus garviae PSL67 and Streptococcus macedonicus PSL72) strains, during the traditional production of cheese at large scale level in six factories located in different areas of Sicily. The cheese making processes were followed from milk to ripened cheeses and the effects of the added LAB were evaluated on the microbiological, chemico-physical and sensorial characteristics of the final products. Results highlighted a high variability for all investigated parameters and the dominance of LAB cocci in bulk milk samples. The experimental curds showed a faster pH drop than control curds and the levels of LAB estimated in 5-month ripened experimental cheeses (7.59 and 7.27 Log CFU/g for rods and cocci, respectively) were higher than those of control cheeses (7.02 and 6.61 Log CFU/g for rods and cocci, respectively). The comparison of the bacterial isolates by randomly amplified polymorphic DNA (RAPD)-PCR evidenced the dominance of the added starter lactococci over native milk and vat LAB, while the added non starter LAB were found at almost the same levels of the indigenous strains. The sensory evaluation showed that the mixed LAB culture did not influence the majority of the sensory attributes of the cheeses and that each factory produced cheeses with unique characteristics. Finally, the multivariate statistical analysis based on all parameters evaluated on the ripened cheeses showed the dissimilarities and the relationships among cheeses. Thus, the main hypothesis of the work was accepted since the quality parameters of the final cheeses were stabilized, but all cheeses maintained their local typicality. Highlights: The effect of LAB was studied on chemico-physical, microbiological and sensory parameters. RAPD-PCR showed the dominance of starter lactococci over native milk and vat LAB. Statistical data revealed dissimilarities among cheeses. The mixture of LAB influenced the characteristics of PDO Pecorino Siciliano cheese.